A giant polymer lattice in a polymer-stabilized blue phase liquid crystal1. Issue 23 (21st June 2015) - Kikuchi, H.; Izena, S.; Higuchi, H.; Okumura, Y.; Higashiguchi, K.
<x xml:space="preserve">Abstract</x> Ultra-small angle X-ray diffraction patterns of a polymer-stabilized blue phase liquid crystal and a possible three-dimensional giant polymer lattice with body-centered cubic O8− symmetry formed in it.